PHARMACOGNOSTICAL STANDARDISATION OF LAGENANDRA TOXICARIA DALZ - Selvakumari, P Annie Sulochana (Malaysian Journal of Science, 2014)
Lagenandra toxicaria Dalz. of Araceae is endemic to South India. It is a semi aquatic herb growing gregariously in semi evergreen forests. By tradition rhizomes are considered carminative, tonic, diuretic and used in bilious complaints. The rhizome extract is said to have insecticidal and antimicrobial properties. Effective utilization of any information requires its systematic evaluation. Pharmacognosy is an important link between pharmacology and medicinal chemistry. Pharmacognostical standards are prepared by systematic study of the drug through morphological and anatomical descriptions of plants, pharmacognostical standards such as structural standards, analytical standards, physical constants and phytochemical analyses. The results of the present investigation provide dependable diagnostic features of the vegetative organs of the plants for the identity of the drug in entire and in fragmentary conditions. Keywords: Lagenandra toxicaria Dalz., pharmacognosy, anatomical characters, physichochemical constants, phytochemical screening